RADIOLOGICAL CRITERIA FOR PATIENT RELEASE FROM CLINIC AFTER RADIONUCLIDE THERAPY OF BRACHYTHERAPY WITH SEALED SOURCE IMPLANTATION - M. I. M.I. Balonov; V. Yu. Golikov; I. A. Zvonova (Радиационная гигиена, 2016)
Dose criteria for limitation of exposure incurred by persons helping the patients or living with patients discharged from hospitals following radionuclide therapy or brachytherapy with implanted sealed radionuclide sources have been proposed for national Russian regulation. By means of a conservative dosimetry model, the values of operational radiological criteria for patient discharge from hospital are substantiated, i.e. whole body activity for radionuclides 125I,131I,153Sm and 188Re as well as dose rate near patient body. Observance of suggested criteria included in the new Russian Standards for Radiation Safety (RSS-99/2009) will ensure radiation safety of people in near environment (family, close friends et ah).